Nectar provision attracts hummingbirds and connects interaction networks across habitats - Ramírez-Burbano, Mónica B.; Amorim, Felipe W. [UNESP]; Torres-González, Alba Marina; Sonne, Jesper; Maruyama, Pietro Kiyoshi (Wiley, 2022)
Many ecosystems have been modified by humans, creating novel habitats that include human-provided resources. Gardens adjacent to native habitats may affect plant–pollinator interactions by altering the determinants of interactions and species specialization. Here, we characterized a network comprising plants and hummingbirds interacting in a birdwatching garden with human-provided resources (nectar feeders and exotic plants) and adjacent Andean cloud forest in Colombia. Specifically, we investigated the proportion of hummingbirds visiting feeders and native/exotic plants to evaluate the connection between the habitats and the ecological determinants of the interaction network. Hummingbirds relied heavily on artificial nectar feeders in the garden, leaving the natural cloud forest for resources. Morphological matching was the single most important predictor of the observed pairwise interactions, for both hummingbirds and plants. At the species level, longer flowering phenology and a higher amount of sugar in nectar led to a higher degree for plants (i.e. the number of visiting hummingbird species). In contrast, a longer floral corolla was associated with lower specialization. Abundance was the best predictor of the number of partners for hummingbirds. The garden created for birdwatching attracted most, but not all, hummingbird species beyond their natural cloud forest habitat. Interestingly, the most frequently visited plants in the garden were native, especially the endemic and endangered tree Zygia lehmannii (Fabaceae). Our results show that some ecological mechanisms determining interactions in natural communities still hold in intensively modified habitats. Furthermore, a compromise between conservation and hummingbirds’ attraction to birding lodges/gardens is possible, for instance by favouring native and endemic plant species that are highly attractive for pollinators.
Keywords: cloud forest; Colombian Andes; ecological fitting; nectar feeders; networks; ornamental plants; pollination; resource provision